UPAYA PENINGKATAN KUALITAS HIDUP LANSIA DI PANTI WERDHA SINTA RANGKANG - Fitriani Ningsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Panti werdha / Jompo is a home or shelter for elderly (elderly). A means by which the elderly are provided with facilities, 24-hour services, activity schedules, and entertainment required as per the elderly. Certainly in the management of nursing homes cannot be separated from the obstacles and difficulties in managing the werdha home. One is the lack of fulfillment of eating and drinking for the elderly, in addition to facing the elderly who are experiencing a decline in health, or psychological disorders such as irritability, difficulty sleeping, depressed, nervous, lonely, impatient, tense, anxious and depressed. This activity aims to improve the quality of life of the elderly through promotive and preventive approaches, namely by conducting elderly health checks such as height measurement, weight, blood pressure, supplementary feeding, and elderly gymnastics and health-related counseling of the elderly. The method used in this activity is the method of counseling, where the counseling is done in Room Hall Panti Werdha Sinta Rangkang. The number of elderly people in Panti werdha Sinta Rangkang that is as much as 80 elderly, but who follow this activity only amounted to 62 people only. Because some elderly there is a sick so it takes a total bedrest. The results achieved from this activity is the implementation of this activity well, collecting data results of health examination of elderly as well as the increasing knowledge of elderly related to the health of elderly.